Mapeamento de epítopos imunogênicos presentes no antígeno amastigota específico A2 de Leishmania donovani e sua utilização como vacina empregando vetor viral - Daniela de Melo Resende (2008)
Leishmaniasis is endemic in many countries in Old an New World. The amastigote specific antigen A2 of Leishmania is a virulence factor shared by L donovani, L. chagasi and L. amazonensis, which are main etiologic agents of visceral and other forms of leishmaniaisis. A2 was also shown to induce protection against experimental Leishmania amazonensis infection in mice. Using predicted hydrophilic as well as class I and II MHC-binding synthetic peptides, we defined the A2 epitopes recognized by antibodies, CD4+ T as well as CD8+ T cells elicited during immunization protocols. Immunization of highly susceptible BALB/c mice with the adenovirus vector expressing A2 (AdA2) resulted in low levels of anti-A2 antibody response, contrasting with high levels of IFN- producing CD4+ T, as well as CD8+ T cells. Further, A2-specific CD8+ T cells from immunized mice were also capable of lysing peptide-sensitized target cells in in vivo cytotoxic assays. Finally, we demonstrated that mice immunized with AdA2 and challenged with 107 live L. chagasi parasites, presented reduced parasite loads at both liver and spleen. Thus, vaccination with AdA2 induces high levels of A2-specific CD4+ T cell as well as CD8+ T lymphocytes that produce high levels of IFN-, display in vivo cytolytic activity, and are associated with protective immunity against murine visceral leishmaniasis.